Fazlur Rahman and the Idea of Islamic Education Reform for Generation Z - selviana safitri; ananda solokhatunnisa; syatia aranni; Herlini puspika sari (Episteme: Jurnal Kajian Mahasiswa, 2025)
The rapid development of digital technology and globalization has significantly influenced the mindset, character, and religiosity of Generation Z. Growing up in a highly digital environment, this generation faces challenges such as moral value shifts, decreasing religious awareness, and the strong influence of popular culture. These conditions require a more contextual and relevant model of Islamic education. This study aims to analyze Fazlur Rahman’s ideas on Islamic educational reform, especially his double movement approach, and to explore their relevance for Islamic education in the digital era. Employing library research supported by content analysis and a historical-philosophical approach, this study finds that Rahman emphasizes contextual Qur’anic interpretation, integration of rationality and morality, the unity of religious and general sciences, and the transformative role of Islamic education. The study concludes that Fazlur Rahman’s educational thought offers a relevant framework for developing Islamic education that fosters critical thinking, ethical awareness, and social responsibility among Generation Z.